2004
DOI: 10.1080/00498250400009171
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disposition of gefitinib, an epidermal growth factor receptor tyrosine kinase inhibitor, in rat, dog and man

Abstract: Following oral administration of [14C]-gefitinib to albino and pigmented rats, radioactivity was widely and rapidly distributed, with the highest levels being found in liver, kidney, lung and gastrointestinal tract, but with only low levels penetrating the brain. Levels of radioactivity persisted in melanin-containing tissues (pigmented eye and skin). Binding to plasma proteins was high (86-94%) across the range of species examined and was 91% in human plasma. Substantial binding occurred to both human serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 17 publications
10
73
1
2
Order By: Relevance
“…Gefitinib has a high volume of distribution in rats (8 -10 L/ kg), dogs (2 -6 L/kg), and cancer patients (1,400 L), which is consistent with pronounced distribution of gefitinib into tissues. This was confirmed by a rat tissue distribution study where gefitinib-related material was found extensively distributed, achieving tissue/blood ratios of >10 in a number of organs, including lung, liver, and kidney (16). Further work to examine distribution into an orthotopic rat lung model is also summarized, together with gefitinib human tumor concentrations generated in a breast cancer study (18), originally presented as a poster at the 40th American Society of Clinical Oncology Annual Meeting in New Orleans (June 2004).…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…Gefitinib has a high volume of distribution in rats (8 -10 L/ kg), dogs (2 -6 L/kg), and cancer patients (1,400 L), which is consistent with pronounced distribution of gefitinib into tissues. This was confirmed by a rat tissue distribution study where gefitinib-related material was found extensively distributed, achieving tissue/blood ratios of >10 in a number of organs, including lung, liver, and kidney (16). Further work to examine distribution into an orthotopic rat lung model is also summarized, together with gefitinib human tumor concentrations generated in a breast cancer study (18), originally presented as a poster at the 40th American Society of Clinical Oncology Annual Meeting in New Orleans (June 2004).…”
Section: Introductionsupporting
confidence: 51%
“…Plasma and tumor extracts were also assayed for gefitinib and its major metabolites (M523595 and M537194) by HPLC with tandem mass spectrometric detection (HPLC-MS/MS). The distribution of radioactivity was also determined in a separate group of female nude mice (bearing LoVo tumor xenografts), which had received four daily oral doses of [ 14 C]-gefitinib at 50 mg/kg (incorporating 500 ACi/kg), by whole body autoradiography of individual mice at various times after the final dose, as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low concentration of gefitinib in the CSF may be attributable to its low permeability at the blood-brain barrier, which affects the delivery of many drugs. It was previously demonstrated that the concentration of [ 14 C]-labeled gefitinib in normal rat brain and spinal cord was only 2% of that in lung, suggesting that gefitinib does not readily cross the bloodbrain barrier (McKillop et al 2004); however, the concentration of gefitinib in the CSF was not measured. Only one previous report considered the concentration of gefitinib in the CSF of NSCLC patients with leptomeningeal metastases (Jackman et al 2006).…”
Section: Discussionmentioning
confidence: 99%